Predicting substance use in emerging adulthood: A genetically informed study of developmental transactions between impulsivity and family conflict. (18th July 2016) - Elam, Kit K.; Wang, Frances L.; Bountress, Kaitlin; Chassin, Laurie; Pandika, Danielle; Lemery-Chalfant, Kathryn
Abstract: Deviance proneness models propose a multilevel interplay in which transactions among genetic, individual, and family risk factors place children at increased risk for substance use. We examined bidirectional transactions between impulsivity and family conflict from middle childhood to adolescence and their contributions to substance use in adolescence and emerging adulthood ( n = 380). Moreover, we examined children's, mothers', and fathers' polygenic risk scores for behavioral undercontrol, and mothers' and fathers' interparental conflict and substance disorder diagnoses as predictors of these transactions. The results support a developmental cascade model in which children's polygenic risk scores predicted greater impulsivity in middle childhood. Impulsivity in middle childhood predicted greater family conflict in late childhood, which in turn predicted greater impulsivity in late adolescence. Adolescent impulsivity subsequently predicted greater substance use in emerging adulthood. Results are discussed with respect to evocative genotype–environment correlations within developmental cascades and applications to prevention efforts.